MEMBANGUN INGATAN INSTITUSIONAL: ARSIP KELEMBAGAAN DI DALAM ORGANISASI SENI: Array - Kiki Rizky Soetisna Putri (Arsip Nasional Republik Indonesia, 2021)
Documenting institutional archives in an art institution is rarely the main discussion. So far, institutional archives have only been assessed in terms of an administrative nature, but in fact, this documentation can be a way to build institutional memories. This paper is an overview of a workshop on institutional archiving in an art organization held at the Asia Art Archive, Hong Kong from 23 to 25 May 2019. The workshop was attended by various art organizations in the Asian region. Furthermore, this paper will use an analytical-qualitative approach to describe archives and institutional archives, management, success parameters, and preservation problems faced, especially for the Asian region which is very unfavorable climatically for several archive mediums. In closing, this paper will link with one of the archiving projects carried out in The Aesthetics & The Sciences of Art Research Group (ASARG), Faculty of Art and Design, ITB called CIVAS (Center for Indonesian Visual Art Studies). keywords: institutional archiving, institutional memory, art organizations, Indonesian visual art